2014
DOI: 10.1186/1742-2094-11-49
|View full text |Cite
|
Sign up to set email alerts
|

The amelioration of phagocytic ability in microglial cells by curcumin through the inhibition of EMF-induced pro-inflammatory responses

Abstract: BackgroundInsufficient clearance by microglial cells, prevalent in several neurological conditions and diseases, is intricately intertwined with MFG-E8 expression and inflammatory responses. Electromagnetic field (EMF) exposure can elicit the pro-inflammatory activation and may also trigger an alteration of the clearance function in microglial cells. Curcumin has important roles in the anti-inflammatory and phagocytic process. Here, we evaluated the ability of curcumin to ameliorate the phagocytic ability of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
(60 reference statements)
2
16
0
Order By: Relevance
“…In the present study, we observed pro-inflammatory M1 activation and a significant decrease in the microglial M2 phenotype in N9 cells after EMF exposure. These findings are consistent with our previous data, which indicated a pro-inflammatory response and a decrease in phagocytosis in EMF-treated N9 cells (He et al, 2014). Notably, as a beneficial intervention, HA treatment significantly suppressed the secretion of pro-inflammatory cytokines and the expression of M1 markers and increases the secretion of anti-inflammatory cytokines and the expression of M2 markers in N9 cells 12 h after EMF exposure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we observed pro-inflammatory M1 activation and a significant decrease in the microglial M2 phenotype in N9 cells after EMF exposure. These findings are consistent with our previous data, which indicated a pro-inflammatory response and a decrease in phagocytosis in EMF-treated N9 cells (He et al, 2014). Notably, as a beneficial intervention, HA treatment significantly suppressed the secretion of pro-inflammatory cytokines and the expression of M1 markers and increases the secretion of anti-inflammatory cytokines and the expression of M2 markers in N9 cells 12 h after EMF exposure.…”
Section: Discussionsupporting
confidence: 93%
“…The 20-min EMF treatment was identified as a threshold condition representing the time of duration beyond which cytotoxicity significantly increases as explained in a previous study (He et al, 2016). In addition, based on the previous time effect experiments of EMF-induced pro-inflammatory responses (Yang et al, 2010;He et al, 2014), the threshold 12-h recovery time after EMF exposure with prominent pro-inflammatory activity was employed in the present study. Clearly, ELISA detection indicated that EMF exposure resulted in increased levels of TNF-α ( Figure 1A), IL-1β ( Figure 1B), but not IL-6 ( Figure 1C), and decreased levels of IL-4 ( Figure 1D) and IL-10 ( Figure 1E).…”
Section: Heat Acclimation Regulates Microglial Polarization In Emf-stmentioning
confidence: 99%
“…In a previous work, we demonstrated that an initial activation and pro-inflammatory response of microglia is induced by EMF exposure [30, 31]. Under the inflammatory conditions, we further observed an alteration in the clearance function of EMF-stimulated N9 cells [9]. Similarly, in this study, we observed an inversed correlation of pro-inflammatory COX-2 and prostaglandin expression with attenuated phagocytosis of 647-fAβ 42 in EMF-stimulated N9 cells.…”
Section: Discussionsupporting
confidence: 84%
“…Additional evidence has revealed that pro-inflammatory cytokines act selectively to regulate the different types of microglial phagocytosis [8]. We previously observed pro-inflammatory responses and a depression of phagocytic activity in EMF-stimulated N9 microglial cells (N9 cells) [9]. However, it remains a central challenge to determine which special cytokines inhibit microglial Aβ clearance after EMF exposure.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][24][25][26][27] It has received extensive attention with its unique effectiveness in glioma therapy. Previous studies demonstrated that Cur can significantly inhibit the proliferation of glioma cells by downregulating multidrug resistance proteins that cause the efflux of many chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%